Study of the mechanism of lithium insertion and depletion in lithium iron phosphate thin films - Möller, Alexander; Justus Liebig University Giessen (My University, 2014)
The mechanism of lithium insertion and depletion in the cathode material lithium iron phosphate (LFP) has been research subject for over a decade. Although being widely-used by now, the exact mechanism still remains unclear. Thin film technology is a method of reducing the complexity of a system in order to study these mechanisms. Firstly, this work presents the preparation of LFP thin films with pulsed laser deposition (PLD). Galvanostatic cycling of thin films prepared on metal substrates was possible for 100 cycles without significant capacity loss. Films prepared on silicon substrates were smooth and covering. Chemical delithiation is compared to electrochemical delithiation. Thin films could still be cycled electrochemically after chemical delithiation. TEM images revealed the size of the primary particles to be less than 20 nm.The preparation process was followed by a detailed electrochemical study via galvanostatic intermittent titration technique (GITT). The study reveals the vanishing of the miscibility gap in nanosized LFP. This effect is attributed to the small size of the primary particles in the film. Furthermore, after the application of a current pulse a concentration gradient remains inside the film even after long relaxation times. Diffusion coefficients of the single-phase LFP were determined. A model for the mechanism of delithiation of the thin film is proposed supporting the model of meta-stable intermediate phases as has been suggested for LFP nanoparticles.An outlook toward a cell for in operando spectroscopy is shown in the last chapter. Proof of principle studies have been conducted and a design for a cell is proposed.

Der Mechanismus der Lithiuminsertion und -extraktion in das Kathodenmaterial Lithiumeisenphosphat (LFP) wird seit über einem Jahrzehnt erforscht. Obwohl dieses Material inzwischen häufig verwendet wird, sind die genauen Mechanismen noch immer ungeklärt.Dünnfilmtechnik ist eine Methode zur Reduktion der Komplexität eines Systems, um solche Mechanismen zu untersuchen. Zunächst wird in dieser Arbeit die Herstellung von LFP Dünnschichten mittels gepulster Laserdeposition (PLD) beschrieben. Galvanostatisches Zyklisieren von Dünnfilmen auf Metallsubstraten über 100 Zyklen war ohne signifikanten Kapazitätsverlust möglich. Dünnfilme auf Siliciumsubstraten waren glatt und deckend. Chemische Delithiierung wird mit elektrochemischer Zyklisierung verglichen. Dünnfilme konnten auch nach chemischer Delithiierung noch elektrochemisch zyklisiert werden. TEM-Aufnahmen zeigen eine Primärpartikelgröße von weniger als 20 nm.Nach der Präparation der Schichten wurden detaillierte elektrochemische Untersuchungen mittels galvanostatisch intermittierender Titrationstechnik (GITT) durchgeführt. Diese Untersuchungen zeigen ein Verschwinden der Mischungslücke in LFP-Dünnfilmen aufgrund der kleinen Partikelgröße. Außerdem bleibt ein Gradient der Lithiumkonzentration auch nach langen Relaxationszeiten. Diffusionskoeffizienten des einphasigen Materials wurden bestimmt und ein Modell der Delithiierung des Dünnfilms wird vorgestellt, das die in der Literatur vorgeschlagene Theorie der metastabilen Zwischenphase unterstützt.Im Sinne eines proof of principle für in operando Spektroskopie werden im letzten Kapitel erste Experimente vorgestellt und ein Zelldesign hierfür wird vorgeschlagen.
Untersuchung des Mechanismus des Lithiumein- und -ausbaus in Lithiumeisenphosphatdünnschichten
Keywords: Dünnschicht; GITT; PLD; Lithiumeisenphosphat; Batterie; thin film; GITT; PLD; lithium iron phosphate; battery; ddc:540